All-Optical Microwave Photonic Downconverter With Tunable Phase Shift - Yunxin Wang; Jingnan Li; Tao Zhou; Dayong Wang; Jiahao Xu; Xin Zhong; Dengcai Yang; Lu Rong (IEEE Photonics Journal)
An all-optical microwave photonic frequency downconverter with tunable full range continuous phase shift is presented. In the proposed system, the radio frequency (RF) and local oscillator (LO) signals modulate two sub Mach–Zehnder modulators (MZMs) in an integrated dual-parallel MZM (DPMZM), respectively. The two sub-MZMs are both biased at the minimum transmission point to implement the carrier-suppressed double-sideband modulation. An optical bandpass filter is then used to retain the +1st order RF and LO sidebands. When the two sidebands are send to a photodetector, an intermediate frequency (IF) signal is produced, and the phase of the converted IF signal is linearly changed by adjusting the bias voltage of the parent MZM in the DPMZM. An experiment is carried out. An RF signal can be downconverted to a phase-tunable IF signal, and the measured spurious-free dynamic range reaches 100.2 dB·Hz2/3. The phase deviation and power ripple of the IF signal are less than 2° and 0.26 dB, respectively. The all-optical design makes the system bandwidth unlimited by electrical components. Meanwhile, since the proposed microwave photonic link can simultaneously implement frequency downconversion and full range phase shift of the converted IF signal, it provides a compact alternative for the applications including radio-over-fiber system and phased-array beamforming.